Subjective Well-Being and Material Deprivation During COVID-19 Pandemic: A Study in Children and Adolescents in Indonesia - Ihsana Sabriani Borualogo; Sulisworo Kusdiyati; Hedi Wahyudi (Faculty of Psychology, Universitas Gadjah Mada, 2022)
This study aimed to investigate the contribution of material deprivation on the subjective well-being (SWB) of children and adolescents aged 10-18 years old during COVID-19 in Indonesia. Participants (N = 3,094; 54.3% girls; 53.2% high school students) were children and adolescents from 33 provinces in Indonesia with mean age = 15.39. Convenience sampling was used in this study, of which data were collected using internet-based questionnaires. SWB was measured using three SWB scales: Children’s Worlds Subjective Well-Being Scale (CW-SWBS), Overall Life Satisfaction (OLS), and one item measures subjective material well-being. Material deprivation was measured by participants’ reports on their accessibility to necessities they need in life. Participants were further asked whether they were worried about their family’s money and access to have food to eat each day. Data were analyzed using linear regression, and descriptive statistics using crosstabs, Chi-Square and ANOVA. Linear regression analysis results showed that material deprivation significantly contributed to lowering SWB scores, lack of access to have food to eat each day, and worrying about family’s money. Participants who experienced material deprivation reported lower SWB scores than those who experienced non-material deprivation. Girls reported lower SWB scores than boys, while older participants reported lower SWB scores than younger ones. Results are discussed using Cummins’ theory of SWB homeostasis. It is suggested that parents play a role as a buffer to assist children and adolescents in adapting to the adverse situation during pandemic COVID-19.